Nonablative fractional laser‐assisted daylight photodynamic therapy with topical methyl aminolevulinate for moderate to severe facial acne vulgaris: Results of a randomized and comparative study. Issue 5 (30th June 2017) - Kim, Tae In; Ahn, Hye‐Jin; Kang, In Hye; Jeong, Ki‐Heon; Kim, Nack In; Shin, Min Kyung
Summary: Background: Photodynamic therapy (PDT) has been reported as an effective alternative treatment for patients with acne. Purpose: To evaluate the efficacy and safety of DL‐PDT in moderate to severe acne and to compare outcomes with those of laser‐assisted daylight photodynamic therapy. Methods: Patients were randomly assigned to either a DL‐PDT group (D group) or a fractional laser‐assisted DL‐PDT group (F group). The outcomes were assessed by measuring acne lesion counts and severity grade at 4, 8, 12, and 16 weeks after therapy commenced. Results: Twenty‐eight subjects completed the study. Compared with baseline, the mean inflammatory lesion counts significantly decreased by 36.0% in the D group and 51.8% in the F group at 8 weeks ( P <.001). The mean acne severity grades in both groups significantly decreased starting at 4 weeks ( P =.012), and the beneficial effects lasted 16 weeks. Conclusion: DL‐PDT with MAL shows clinically good responses to inflammatory lesions and is well tolerated in patients with moderate to severe acne.